Atorvastatin Exerts Antileukemia Activity via Inhibiting Mevalonate-YAP Axis in K562 and HL60 Cells - Zhang, Lei; Chen, Ting; Dou, Yonghai; Zhang, Shaolu; Liu, Hongyan; Khishignyam, Tungalagtamir; Li, Xiaofei; Zuo, Duo; Zhang, Zhe; Jin, Meihua; Wang, Ran; Qiu, Yuling; et al. (Frontiers in Oncology, 2019)
Novel therapeutic strategies are still urgently expected for leukemia despite undisputed success of various targeted therapeutics. The antileukemia activity of Atorvastatin, a 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor, on human leukemia cells was investigated. Atorvastatin inhibited K562 and HL60 cell proliferation, induced G2/M cell cycle arrest in K562 cells by down-regulating cyclinB1 and cdc2, but G0/G1 arrest in HL60 cells by up-regulating p27 and down-regulating cyclinD1 and p-pRb. Atorvastatin also induced apoptosis in both cell lines, in which the reactive oxygen species (ROS)-related mitochondrial apoptotic signaling might be involved, with increase of ROS and Bax/Bcl-2 ratio, loss of mitochondrial membrane potential (MMP), release of cytochrome C into cytosol, and activation of Bax/Caspase-9/Caspase-3/PARP pathway. Inhibition of YAP nuclear localization and activation by Atorvastatin was reversed by the addition of mevalonate, GGPP, or FPP. Further, the effects on cell cycle arrest- and apoptosis- related proteins by Atorvastatin were alleviated by addition of mevalonate, suggesting the antileukemia effect of Atorvastatin might be through mevalonate-YAP axis in K562 and HL60 cells. Our results suggest that Atorvastatin might be used for leukemia therapy while evidence of clinical efficacy is required.